Partner communication behaviors and diurnal cortisol patterns - Seiter, Natasha, author; Lucas-Thompson, Rachel, advisor; Quirk, Kelley, committee member; Henry, Kim, committee member (Colorado State University. Libraries, 2019)
Previous research suggests that diurnal cortisol patterns are associated with marital communication behaviors reported in naturalistic settings (e.g., Stawski, Cichy, Piazza, & Almeida, 2013), and observed communication behaviors are associated with acute cortisol responses to marital conflict laboratory tasks (e.g., Feinberg et al., 2013). However, it is unclear how observed marital communication behaviors are linked to individuals' typical diurnal cortisol patterns. The goal of this study was to investigate whether partners' ratios of observed positive to negative communication behaviors, self-reported marital conflict, and/or self-reported resolution predict diurnal cortisol patterns. Participants were heterosexual couples (n=124) who engaged in a conflict discussion which was videotaped and coded for negative and positive communication behaviors and reported marital conflict. Cortisol samples were taken across two days for each individual. Results of structural equation model analyses suggested that men's greater observed communication quality predicted women's higher cortisol intercepts and men's steeper slopes, men's greater self-reported marital conflict predicted women's lower intercepts, and, in some models, women's greater reported resolution predicted women's lower intercepts and men's steeper slopes. Overall, these findings suggest that less positive and more negative marital conflict is a stressor that contributes to dysfunctional functioning of the stress system. Implications of this research for couples' therapy practice are discussed.